Case Report: Analysis of four cases of metastatic bladder masses after radical prostatectomy - Wang, Hao; Xie, Dawei; Lu, Jun; Chu, Yifan; Wang, Siqi; Qiao, Peng; Wu, Liyang; Wang, Jianwen (Frontiers in Oncology, 2023)
Objective The aim of this study is to investigate the clinical characteristics and diagnostic and therapeutic methods of bladder metastasis after radical prostatectomy and to improve its diagnosis and treatment. Methods The clinical data of four patients with bladder metastasis after radical prostatectomy were retrospectively analyzed from January 2011 to December 2021. Three cases suffered from intermittent gross hematuria, and only one case was found to have an elevated prostate-specific antigen (PSA) value. Transurethral resection of bladder tumor was performed in four cases, in which one case also underwent resection of urethral mass. Three cases received endocrine therapy, one of which added intravesical instillation and radiation therapy. Another case received chemotherapy based on comprehensive treatment. Results According to the pathological and immunohistochemical results, three cases were acinar adenocarcinoma of the prostate with Gleason score of 9, and all cases were PSA positive and negative for cytokeratin 7 (CK7) and GATA binding protein 3 (GATA-3). One case was small cell neuroendocrine carcinoma of the prostate and was positive for chromogranin A (CGA), synaptophysin (SYN), and cluster of differentiation 56 (CD56). During the follow-up period of 4 to 13 months, one case was lost to follow-up and three cases were alive. Conclusion Bladder metastasis after radical prostatectomy is rare, and pathology combined with immunohistochemistry is the gold standard for its diagnosis. Pathological type determines its treatment. Systemic treatment is essential, and local treatment is the most palliative means. Early diagnosis and treatment is significant for better prognosis.